ANALISIS PELATIHAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN (STUDI PADA BAGIAN SEWING DAN BAGIAN POTONG DI PT. SANDANG ASIA MAJU ABADI) - Sefrina Zafira Riski; Agus Hermani (Jurnal Ilmu Administrasi Bisnis, 2019)
This research was aims to determine how to improve employee competency on PT. Sandang Asia Maju Abadi through job training to improve employee performance. The  frame in this study to use the ADDIE Model which is a Learning Organizing program. The program would be an analytical tool for the answering research problems. The method used is a qualitative approach and uses data collection techniques through by observation and interviews. Interviews were on 3 speakers, the Production Manager, Chief Supervisor, and Production Staff. The results of this research that the Analyze and Development is done well. However, in the application of Design, Implementation and Evaluation is not good. So, the advice given is in the Design should all new employees put in one Line, in the Implementation should the material of the work introduction training program can doing at least 3 days and in the Evaluation should can doing in each phase Analyze, Design, Development and Implementation phase to repairs at each stage .